Futures contracts: analysis of the current state and prospects of development in the Russian market ("Journal "U". Economy. Management. Finance.", 2025)
The article discusses futures contracts as an important tool of the modern financial market. The analysis of their role in risk hedging, speculative operations and the formation of price targets is carried out. Statistical data on the volume of futures trading in the Russian market for the period 2021-2024 are presented, the main trends and development prospects are identified. The study includes an analysis of real-world examples of the use of futures contracts to hedge risks by enterprises in various industries.
Keywords: futures contracts; hedging; speculation; financial market; derivatives; stock trading; risk management